A Descriptive Study of Children’s Dietary Habits and Nutritional Status - Patmawati; Sumarmi; Ernawati; Nuryana, Riska; Alwi; Syamsinar (Bantayang Omni Cendekia, 2026)
Background: Children’s physical and mental health depends on a balanced diet that provides adequate nutrients to support optimal growth and development. Objective: This study aimed to describe children’s dietary habits and their nutritional status. Methods: This study employed a descriptive method with a cross-sectional design involving 59 elementary school students. Data were collected using a dietary questionnaire and anthropometric measurements, and analyzed descriptively using frequency and percentage distributions. Results: More than half of the respondents had appropriate dietary habits (55.9%) and normal nutritional status (57.6%). Among children with appropriate dietary habits, the majority had normal nutritional status (93.9%). In contrast, children with inappropriate dietary habits were more likely to experience undernutrition (42.3%) and overnutrition (46.2%). Conclusion: Appropriate dietary habits are associated with better nutritional status among children. Therefore, balanced and regular food intake, including essential nutrients such as carbohydrates, proteins, vitamins, and minerals, is important to support optimal child health.